Pengaruh Servant Leadership dan Budaya Organisasi Terhadap Komitmen Organisasional Yang Dimoderasi oleh Kepuasan Kerja Pada Satuan Kerja Pelaksanaan Jalan Nasional Wilayah IV Provinsi Sumatera Utara - Simamora, Melianawati; Ardiani , Winda; Fahlevi, Alvin (Jurnal Ekonomi Bisnis Digital, 2022)
The purpose of this study was to determine the effect of servant leadership and organizational culture on organizational commitment in Satuan Kerja Pelaksanaan Jalan Nasional Wilayah IV Provinsi Sumatera Utara. And to find out whether job satisfaction can strengthen the relationship between servant leadership and organizational culture towards organizational commitment in Satuan Kerja Pelaksanaan Jalan Nasional Wilayah IV Provinsi Sumatera Utara. This type of research is associative research. The population in this study is the number of employees in Satuan Kerja Pelaksanaan Jalan Nasional Wilayah IV Provinsi Sumatera Utara, totaling 130 people who focus on employees in the field of general administration and human resources (HR) and the sample used in this study is a saturated sample of 130 respondents. The data analysis technique in this research is Moderating Regression Analysis (MRA). The results showed that servant leadership had a positive and significant effect on organizational commitment, and organizational culture had a positive and significant effect on organizational commitment. Based on the results of the MRA statistical test, it was found that job satisfaction variable was a moderator in the relationship between servant leadership and organizational commitment, and job satisfaction variable was also a moderator in the relationship between organizational culture and organizational commitment.